ความสัมพันธ์ระหว่างภาวะผู้นำกับการนำปรัชญาเศรษฐกิจพอเพียงไปประยุกต์ใช้ในการบริหารจัดการโรงเรียนประถมศึกษาสังกัดสำนักงานเขตพื้นที่การศึกษาประถมศึกษานครพนม เขต 2 - Seehabut, Nopphalit; Puangyod, Pitoon; Hanrin, Chanwit (Journal of Graduate School Sakon Nakhon Rajabhat University, 2021)
This research aimed to: 1) examine leadership under the Nakhon Phanom Primary Educational Service Area Office 2; (2) investigate the application of sufficiency economy philosophy for primary school management; 3) determine the relationship between leadership and application of sufficiency economy philosophy for primary school management; and 4) identify the predictive equations of leadership affecting the application of sufficiency economy philosophy for primary school management. The sample group consisted of school administrators and teachers, yielding a total of 316 participants. The research instrument was a set of questionnaires. The statistics for data analysis were percentage, mean, standard deviation, Pearson's product-moment correlation coefficient, and Stepwise multiple regression analysis. The research results revealed that: 1. the level of leadership under the Nakhon Phanom Primary Educational Service Area Office 2 was overall at a high level. 2. the level of application of sufficiency economy philosophy for primary school management was overall at a high level. 3. the correlation coefficient of leadership and application of sufficiency economy philosophy for primary school management were at a high level. 4. leadership in terms of teaching supervision and evaluation, environment and culture arrangement for conducive learning, curriculum management and development, and student potential development was able to predict the application of sufficiency economy philosophy for school management at 71 percent. The predictive equations was written as follows: = -.22 + 0.47X4 + 0.19X2 + 0.18X 5 + 0.17X3 y = 43Z X4 + 0.18Z X5 + 0.16Z X2 + 0.15Z X3